Not So Sweet: Translating and Re-TranslatingBianciardi’s La Vita Agra - Mulry, Peter Thomas (Jan Kochanowski University Press, 2024)
This paper attempts to provide a theoretical consideration of the strategies employed in my translation of Luciano Bianciardi’s 1962 novel La Vita Agra into English. A brief review of the multiple connotations of context and its relation to translation precedes an attempt to define Bianciardi’s literary style and discuss some specific areas of difficulty encountered in rendering the novel’s style in English, focusing on grammatical and syntactical equivalence, and the role of Italian dialect. Throughout, Eric Mosbacher’s 1965 English translation has been used as a point of comparison. The paper concludes with a more extended discussion of the wider intertextual system in which La Vita Agra can be located, and the possible implications this has for a translation of the novel.